EL USO DE LA METODOLOGÍA DE CASOS EN LA FORMACIÓN DE ADMINISTRADORES Y CONTADORES - Rusque, Ana María (La Sociología en sus Escenarios, 2010)
Abstract. The objective of this communication is to present/display some reflections on the relevance of the use of the Methodology of Cases in the formation of the professionals who prepare themselves to work in organizations, especially administrators and accountants who will be able to evolve like executives at different levels from the organization. Resumen. Presentación de una pedagogía de enseñanza aprendizaje de una metodología de investigación cualitativa (metodología de casos) que permite formar a unos futuros profesionales de las áreas administrativas.